2005
DOI: 10.1103/physrevd.72.126004
|View full text |Cite
|
Sign up to set email alerts
|

Multibrane inflation and dynamical flattening of the inflaton potential

Abstract: We investigate the problem of fine tuning of the potential in the IKLIMT warped flux compactification scenario for brane-antibrane inflation in Type IIB string theory. We argue for the importance of an additional parameter ψ0 (approximated as zero by IKLIMT), namely the position of the antibrane, relative to the equilibrium position of the brane in the absence of the antibrane. We show that for a range of values of a particular combination of the Kähler modulus, warp factor, and ψ0, the inflaton potential can … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
85
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(89 citation statements)
references
References 49 publications
4
85
0
Order By: Relevance
“…Discrete symmetries can be used to forbid problematic mass terms [652], and in some cases have been shown to be compatible with moduli stabilization [657]. Dynamical mechanisms have also been found: it was shown in [653,655] that if N D3-branes become trapped in a metastable 13 The restriction to irrelevant perturbations in [553] rests on the requirement that the background throat solution is a good approximation in the infrared. However, [42,534] showed that certain relevant perturbations are necessarily present in Klebanov-Strassler regions of KKLT compactifications.…”
Section: Fine-tuningmentioning
confidence: 99%
See 1 more Smart Citation
“…Discrete symmetries can be used to forbid problematic mass terms [652], and in some cases have been shown to be compatible with moduli stabilization [657]. Dynamical mechanisms have also been found: it was shown in [653,655] that if N D3-branes become trapped in a metastable 13 The restriction to irrelevant perturbations in [553] rests on the requirement that the background throat solution is a good approximation in the infrared. However, [42,534] showed that certain relevant perturbations are necessarily present in Klebanov-Strassler regions of KKLT compactifications.…”
Section: Fine-tuningmentioning
confidence: 99%
“…Considerable effort has been directed at finding mechanisms that can alleviate the fine-tuning of the potential in warped D-brane inflation -see [38,[651][652][653][654][655][656]. Here, we will outline a few of the leading approaches.…”
Section: Fine-tuningmentioning
confidence: 99%
“…This idea was later extended into the scenario of multiple brane inflation and appeared in Refs. [12,13] (see [14,15] for earlier studies under slow-roll approximation). A distinguishing feature of the model in this type is that a large positive nonlocal non-Gaussianity can be obtained due to an enhancement of a small sound speed for the perturbation [16,17], which is in contrast to the prediction of a canonical single-field inflation model [18].…”
Section: Introductionmentioning
confidence: 99%
“…With the great success of inflationary cosmology in explaining the spectrum of cosmic microwave background (CMB) fluctuations [1][2][3][4], as well as recent progress in understanding inflation in string theory -see, for example, [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]-the time is ripe to ask what signals string theory might have in cosmology. Historically speaking, there has not been much cause for optimism.…”
Section: Introduction: Seeing Strings In Cosmologymentioning
confidence: 99%